Analysis of water and sediment quality in Pacific white leg shrimp Litopenaeus vannamei culture with different sediment redox potential - Wiyoto Wiyoto; Andri Hendriana; Ridwan Siskandar; Nurul Mashita; Tangkas Mahendra; Arif Dwi Cahyo; Jibal Rizki Akbar Arzi; Salsabila Setya Aulia; Julie Ekasari (Jurnal Akuakultur Indonesia)
ABSTRAK